2014
DOI: 10.3892/mmr.2014.2345
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference targeting inhibition of S100A4 suppresses cell growth and promotes apoptosis in human laryngeal carcinoma Hep-2 cells

Abstract: Abstract. S100A4 is a small Ca 2+ binding protein that belongs to the S100 family and is involved in a number of cellular functions, including cell cycle control, proliferation, apoptosis, and has a significant role in angiogenesis and neurite extension. However, the exact function and mechanism of S100A4 in laryngeal carcinogenesis remains to be elucidated. The present study was designed to investigate the potential use of RNA interference to inhibit S100A4 expression and activation, as well as the subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…We show for the first time that normal CD34 + cells and myeloid differentiated lineages express this protein in the cytosol. Knocking down expression of S100A4 in AML lines results in cell death through induction of apoptosis and hence is an attractive target for cancer therapy particularly in AML given that normal cells would be spared [62]. Increasing evidence suggests that expression and subcellular localization of several S100 proteins is different between physiological and pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…We show for the first time that normal CD34 + cells and myeloid differentiated lineages express this protein in the cytosol. Knocking down expression of S100A4 in AML lines results in cell death through induction of apoptosis and hence is an attractive target for cancer therapy particularly in AML given that normal cells would be spared [62]. Increasing evidence suggests that expression and subcellular localization of several S100 proteins is different between physiological and pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Results from previous studies indicate that RNA interferencemediated knockdown of S100A4 leads to apoptosis of laryngeal cancer cells. 34 Levine suggested that increased apoptosis in Hep-2 cells transfected with S100A4-RNA interference contributes to the reduction of cell numbers. 35 Previous data demonstrates that S100A4 interacts with the tumor suppressor p53 to affect cell growth and p53dependent apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…There is little data demonstrating the function of RNA interference‐mediated silencing of S100B in hippocampal cell apoptosis. Results from previous studies indicate that RNA interference‐mediated knockdown of S100A4 leads to apoptosis of laryngeal cancer cells . Levine suggested that increased apoptosis in Hep‐2 cells transfected with S100A4‐RNA interference contributes to the reduction of cell numbers .…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptome analysis revealed several genes, which are associated with the regulation of cell survival such as S100A4 and SYK, both of which were upregulated in EJ28P. Incidentally, S100A4 expression is positively regulated by the Wnt/β-catenin signalling pathway [ 40 ] to protect cells from pro-apoptotic stimuli [ 41 , 42 ]. It was reported that the knockdown of S100A4 decreased cellular proliferation and promoted apoptosis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Incidentally, S100A4 expression is positively regulated by the Wnt/β-catenin signalling pathway [ 40 ] to protect cells from pro-apoptotic stimuli [ 41 , 42 ]. It was reported that the knockdown of S100A4 decreased cellular proliferation and promoted apoptosis [ 42 ]. Meanwhile, the SYK gene was reported to provide pro-survival signals [ 43 ] whereas the inhibition of its protein expression resulted in apoptosis and the suppression of cellular proliferation [ 44 ].…”
Section: Discussionmentioning
confidence: 99%